Decellularized Aortic Scaffold Alleviates H2O2-Induced Inflammation and Apoptosis in CD34+ Progenitor Cells While Driving Neovasculogenesis. (10th February 2020) - Gao, Liping; Feng, Anqi; Li, Cui; Schmull, Sebastian; Sun, Hong
Abstract : Bone marrow-derived stem/progenitor cells have been utilized for cardiac or vascular repair after ischemic injury, but they are subject to apoptosis and immune rejection in the ischemic site. Multiple scaffolds were used as delivery tools to transplant stem/progenitor cells; however, these scaffolds did not show intrinsically antiapoptotic or anti-inflammatory properties. Decellularized aortic scaffolds that facilitate cell delivery and tissue repair were prepared by removing cells of patient-derived aortic tissues. Scanning electron microscopy (SEM) showed cells attached well to the scaffold after culturing for 5 days. Live/dead staining showed most seeded cells survived at day 7 on a decellularized aortic scaffold. Ki67 staining demonstrated that decellularized aortic scaffold promoted proliferation of bone marrow-derived CD34+ progenitor cells. Apoptosis of CD34+ progenitor cells induced by H2 O2 at high concentration was significantly alleviated in the presence of decellularized aortic scaffolds, demonstrating a protective effect against oxidative stress-induced apoptosis. Furthermore, decellularized aortic scaffolds significantly reduced the expression of proinflammatory cytokines (IL-8, GM-CSF, MIP-1 β, GRO- α, Entoxin, and GRO) concurrently with an increase in anti-inflammatory cytokines (IL-2 and TGF- β ) released from CD34+ progenitor cells when exposed to H2 O2 at low concentration. Finally, neovascularization was observed by H&E and immunohistochemical staining 14 days after the decellularized aortic scaffolds were subcutaneously implanted in nude mice. This preclinical study demonstrates that the use of a decellularized aortic scaffold possessing antiapoptotic and anti-inflammatory properties may represent a promising strategy for cardiovascular repair after ischemic injury.